Determining the changes in the sustainable livelihoods of informal settlements in the city of Cape Town metropolitan from 2001 and 2011 - Mbatha, Lethiwe Slindi (Stellenbosch : Stellenbosch University, 2019)
Thesis (MA)--Stellenbosch University, 2019.